Implementasi Integrasi Pendidikan Salaf dan Khalaf dalam pemikiran KH. Najib Salimi di Pondok Pesantren Al-Luqmanniyyah Yogyakarta - Suharno Noto Anom Indratmojo (STAI Ihyaul Ulum Gresik, 2019)
Al-Luqmaniyyah Islamic boarding school has a special phenomenon compared to other salaf Islamic boarding schools. Al Luqmaniyyah Islamic boarding school is located in an urban center area full of development and modernization in several social and cultural aspects. That is one of the supporting factors students in Al-Luqmaniyyah Islamic Boarding School. They are student who is studying on Yogyakarta's campus areas. Even though most of the santri are students, they are still have many other activities. They lives with a system of forgiveness, such as santri are encouraged to do ascetic practice, riyadoh and mujahadah. Things that more interesting are viewed from the figure of the kiyahi. KH. Najib Salimi, who have a less formal educational background, leads Al Luqmaniyyah become a great school. This is extraordinary, he was able to run the wheels of Islamic boarding school education with a state of santri that was so intellectually and modernly advance. This research is a qualitative research. Data was analyzed using inductive mindset. That is an analysis which tends to use words to explain phenomenas or datas that are still in general towards some conclusions that are more specific. The results of the study show that in order to maintain its existence among others, Al-Luqmaniyyah Islamic Boarding School integate liafe changes without eliminating the existence of noble traditions in order to maintain virtue of each and everyone of them. This was a caregiver policies in developing the curriculum and managerial of this school. That includes: allocation of learning time, learning strategies and methods, leadership and learning facilities.